Comparable Efficacy of Some IPM Packages on the Suppression of Pod Borer (Euchrysops cnejus) in Yard Long Bean - Akter, M. M. Rahman*, S.M.M. Rahman and A. (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> A study was undertaken to evaluate the effectiveness of some IPM tools for the suppression of pod borer (Euchrysops cnejus) attacking yard long bean. The experiment was conducted at She-e-Bangla agricultural University, Sher-e-Bangla Nagar Dhaka, during March to September 2007 & comprised of nine treatments. Those were T1: Mechanical control (hand picking of larvae) at 7 days interval; T2: Neem oil @ 5ml/ L of water at 7 days interval; T3 : Neem oil @ 5 ml /L of water + Mechanical control at 7 days interval; T4 : Suntap 50 SP@ 3 g /L of water at7 days interval; T5 : suntap 50 SP @ 3 g /L of water +Mechanical control at 7days interval; T6 : Shobicron 425 EC @ 2 ml / L of water at 7 days inrterval ; T7: Shobicron 425 EC @ 2 ml /L of water +Mechanical control at 7 days interval; T8: Neem seed kernel @ 10 g /L of water + Mechanical control at 7 days interval & T9: Untreated control. Data recorded on infestation level, yield contributing characters & yield of yard long bean revealed that performance of treatment T3 (Neem oil @ 5 ml /L of water + Mechanical control at 7 days interval) was superior throughout the season as compared to others; the lowest performance in the control treatment (T9). The highest healthy pods by number (59.80) & by weight (993.87 g), similarly the lowest infestation per plant by number (7.06 %) & by weight (72.62 g) was recorded in T3 treatment. The highest healthy pod length (54.20 cm) the height length of edible portion (48.64 cm) of partially infested pod, the highest yield (22.15 ton /ha) was recorded in the T3 treatment; while the lowest healthy pod length (44.60 cm), lowest edible portion (30.11cm) of partially infested pod and the lowest yield (14.74 ton / ha) was recorded in the control treatment (T9). The highest benefit cost ratio (3.53) was recorded in the T3 treatment while the lowest benefit cost ratio (1.23) in T8 treatment.